From consultation to participation in public health research: reflections on a community-based research partnership - Breen, Lauren; O'Connor, Moira (BioMed Central, 2014)
Background - Road traffic crashes and their outcomes are substantial global public health issues and public health initiatives are increasingly involving relevant community members in order to create sustainable change. This paper describes an applied research project utilizing participatory methods to establish a road trauma support service in Western Australia and reflects on the extent of participation in the community-based research partnership. Community-based participatory research (CBPR) provided the basis for the research project conducted in partnership with 34 government and non-government agency representatives and people affected personally by road trauma and which resulted in 22 recommendations for establishing the service. Findings - Attempts to position the group as co-researchers highlighted the dynamic interplay of factors that hinder and enable participation in participatory research. Barriers to participation within the research process included the limited time and funds, reluctance to share authorship, and a lack of clarity regarding roles and processes. Factors that enabled participation were the recognition of each member’s expertise, providing different forms and methods of communication, and the reimbursement of costs according to role. Discussion - In May 2012, the Government of Western Australia announced it would fund the recommendations and Road Trauma Support Western Australia was launched in November 2013. Notwithstanding this successful outcome, there were varied experiences of participation in the research process, and this was despite the use of a research methodology that is by definition participatory, with explicit and embedded participatory structures and processes. The research project shows that elements of CBPR can be incorporated into public health research, even in projects with externally-imposed time and budget constraints.